ISU PRIMORDIALISME DAN KOMUNIKASI POLITIK DALAM PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN TAHUN 2014 (Studi Kegagalan Prabowo-Hatta pada Pemilihan Umum Presiden dan Wakil Presiden 2014 di Kabupaten Banyumas) - Meta Dyah Puspita; Susilo Utomo; Nunik Retno Herawati (Journal of Politic and Government Studies, 2016)
There is an interesting fact when Indonesian Presidential election 2014 was holding on at Banyumas Regency where one candidate that is Prabowo Subianto who was born and had Banyumas’s blood line were losing his chance to be Indoneisan President for 2014-2019 in his hometown. Prabowo is partner to Hatta Rajasa (Prabowo-Hatta) only gained 346 345 votes from total valid votes that is 959 571 votes, only get 36.09% votes and they got failed 27 Districts in Banyumas Regency. Since his firts candidacy, he is predicted to be Indonesian President of from Banyumas when he win that election. Some banners are blooming on the road which show and give another support to Praboso Subianto by writing down “Banyumas Descent, Leads Indonesia” it means the Banyumas people who lead Indonesia. By this research, the authors used a qualitative descriptive design methods, the research to draw on a carefully about specific individuals or groups on the circumstances and symptoms. Research results show that the cause of failure Prabowo Hatta in Banyumas, among others: Team Success is deemed not solid and just run what was outlined by the DPP, brought the primordialism issue on the ground which is where ancestral Prabowo is an innovation, but should not only it is implemented. In this case the process of political communication, political marketing execution by bringing personal branding and primordial issues are considered less effective and less able to meet the tastes of the public choose. Keywords: Primordialism Issues, Political Communication, Political Marketing, Personal Branding, Failure